Ingeborg Bachmanns 'Ein Ort für Zufälle' - Däufel, Christian (De Gruyter, 2013)
Ingeborg Bachmanns Berlin-Text
10.1515/9783110280555
Keywords: 20. Jh; 20th Century; Bachmann; Ingeborg; Berlin Literature; Berlin-Literatur; Commentary; Kommentar; LITERARY CRITICISM / European / German